Role of Fine Needle Aspiration Cytology (FNAC) in Preoperative Diagnosis of Parotid and Submandibular Gland Neoplasm (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: The overall incidence of salivary gland neoplasm is 2.5-3.0 per 100000 per year. Salivary gland malignancies account for about 5% of head-neck malignancies. Though, it is uncommon but not rare in our country. Fine Needle Aspiration Cytology (FNAC) has been widely used for many years as a method for assessing salivary gland lesion preoperatively. It is a simple, quick, inexpensive and minimally invasive technique used to diagnose different types of salivary gland neoplasm.Objectives: To see the frequency of malignancy in parotid and submandibular salivary gland neoplasm and also to find out the role of FNAC in their preoperative diagnosis. Histopathological examination of the resected parotid and submandibular gland neoplasm was considered as gold standard to compare FNAC report of this study.Methods: This was a cross – sectional study which was conducted in the Department of Otolaryngology – Head & Neck Surgery, Dhaka Medical College Hospital, Dhaka from January 2017 to June 2018. Purposive sampling method was used to collect data. Pre-tested structured data sheet was used to record information. After collection, data were edited by meticulous checking and re-checking. Data were analyzed using SPSS for windows version 22.Results: After histopathological confirmation of the resected specimen, most common benign parotid tumour was pleomorphic adenoma 76.7% followed by warthin’s tumour 16.7%. In benign submandibular gland neoplasm, pleomorphic adenoma was the commones 87.5% followed by haemangioma 12.5%. Commonest malignant tumour of submandibular gland was adenoid cystic carcinoma 50.0%. In our study sensitivity of FNAC was 75.0%, specificity 94.74% and overall accuracy was 90%. Positive predictive value and negative value were 81.82% and 92.31% respectively.Conclusion: It can be concluded that fine needle aspiration cytology is a safe, cheap and useful preoperative diagnostic tool in the diagnosis of malignancy in parotid and submandibular gland, but as fine needle aspiration cytology partly depends on operator skill, it may give false negative and false positive result.Bangladesh J Otorhinolaryngol 2021; 27(2): 124-129